The Role of Librarians in Preventing Plagiarism in Higher Education: Case Studies at Diponegoro University, State University of Semarang, and Dian Nuswantoro University - Tarmiasih, Tarmiasih; Azizah, Ika Nur (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2025)
Background: Plagiarism violates academic integrity and includes submitting others’ work without proper acknowledgment. In higher education, librarians play a crucial role in its prevention. This study examines the role of librarians in preventing plagiarism at Diponegoro University, State University of Semarang, and Dian Nuswantoro University. Although similar studies have been conducted previously, none have specifically explored the role of librarians in preventing plagiarism from the perspectives of academic librarians at these three institutions.Objective: This study aims to explore the role of librarians in preventing plagiarism at higher education institutions at three higher education institutions: Diponegoro University, State University of Semarang, and Dian Nuswantoro University.Methods: This study uses a qualitative method with a case study approach. Data were collected through semi-structured interviews, observations, and document analysis. Informants were selected using purposive sampling. This study involved six librarians as informants, consisting of two librarians from each of the three universities. Data analysis was conducted using within-case analysis and cross-case analysis.Results: The findings indicate that librarians play several roles in preventing plagiarism. These roles include sharing information, providing guidance or consultation, conducting training or instruction, offering plagiarism detection services, and collaborating with external parties. The study also identified various challenges librarians face in carrying out these roles.Conclusion: Overall, librarians have implemented various efforts to prevent plagiarism effectively. However, this research only involved librarians and was limited at three higher education institutions. It is therefore recommended that future research includes other stakeholders, such as students and lecturers, and expands the research scope to gain a more comprehensive understanding and develop broader, applicable solutions.